Impact of BMI on IL-6 and IL-18 levels in children and adolescents with asthma - Regina N. Khramova; Elena V. Tush; Tatyana I. Eliseeva; Dmitriy Yu. Ovsyannikov; Svetlana V. Krasilnikova; Maxim A. Karpenko; Natalia A. Geppe; Nailya I. Kubysheva; Olga V. Khaletskaya (Exploration of Medicine)
Aim: To study the effect of body mass index (BMI) on interleukin (IL)-6 and IL-18 levels in children and adolescents with bronchial asthma (BA), taking into account the presence or absence of bronchial obstruction. Methods: A single-center observational cross-sectional pilot study was conducted. Eighty-six patients with BA aged from 8 to 17 years were studied. Anthropometric and spirometric parameters and IL-6, IL-18 levels were assessed. The study participants were divided into 2 groups: 1—patients with normal body weight (BW), 2—overweight/obese. Results: The serum levels of IL-6 and IL-18 were statistically significantly higher in overweight/obese patients than in normal BW patients, being 1.18 [0.10; 3.27] pg/mL vs. 0.52 [0.10; 1.34] pg/mL, P = 0.036 and 251.0 [207.0; 346.0] pg/mL vs. 208.0 [134.0; 293.0] pg/mL, P = 0.012, respectively. Statistically significant direct correlations of IL-6 and IL-18 with z BMI were obtained in the total group: R = 0.35, P = 0.001; R = 0.37, P = 0.002, respectively. In the overweight/obese group, IL-6 and IL-18 levels were statistically significantly higher in patients with obstruction [z forced expiratory volume in one second (FEV1)/forced vital capacity (FVC) < –1.645 z] than in patients without obstruction (z FEV1/FVC > –1.645 z), respectively: 1.74 [1.10; 5.41] pg/mL vs. 0.59 [0.50; 1.48] pg/mL, P = 0.026 for IL-6 and 298.50 [207.00; 425.00] pg/mL vs. 234.50 [207.00; 300.00] pg/mL, P = 0.046 for IL-18. Conclusions: In patients with BA and overweight/obese, but not in patients with BA and normal BW, the presence of bronchial obstruction is associated with higher serum levels of IL-6, IL-18. This may indicate the involvement of these ILs in the genesis of bronchial obstruction in patients with BA and overweight/obese.